2001
DOI: 10.1016/s0306-5456(01)00217-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative assessment of women's experience of a one-stop menstrual clinic in comparison with traditional gynaecology clinics

Abstract: Objective A quantitative and qualitative evaluation of the views of patients attending two types of clinics for menstrual disorders. Methods Semi-structured qualitative interview and quantitative questionnaire.Setting Five traditional general gynaecology clinics and a one-stop menstrual clinic, where investigations are performed and results given to patients on the same day.Participants Two hundred and thirty-nine women (126 from the gynaecology clinic and 113 from the menstrual clinic) were recruited into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 3 publications
0
28
0
Order By: Relevance
“…One Stop screening services have been shown to reduce patient anxiety for breast and gynaecological problems in the short term [17][18][19][20], but some have argued that the lack of demonstrable long-term benefit in addition to the increased cost to the NHS of same day reporting of test results means that OS screening can not be justified [19]. This study did find important benefits of OS clinics over their AH counterparts: patients received more comprehensive screening and attended their screening appointments more regularly.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…One Stop screening services have been shown to reduce patient anxiety for breast and gynaecological problems in the short term [17][18][19][20], but some have argued that the lack of demonstrable long-term benefit in addition to the increased cost to the NHS of same day reporting of test results means that OS screening can not be justified [19]. This study did find important benefits of OS clinics over their AH counterparts: patients received more comprehensive screening and attended their screening appointments more regularly.…”
Section: Discussionmentioning
confidence: 68%
“…In response to this, OS clinics have been introduced in a variety of clinical settings in an attempt to reduce patient anxiety and improve attendance rates [17]. A number of studies comparing women attending OS screening clinics compared to standard treatment clinics for the investigation of breast and gynaecological problems have demonstrated that anxiety is reduced over the short-term (from 24 h post screening up to 1 week) [17][18][19][20]. The possible benefit of OS Table 1 Screening protocol for vHL patients and 'at risk' family members [11] vHL manifestation Screening required…”
Section: Introductionmentioning
confidence: 99%
“…Outpatient hysteroscopy in our study was performed in over 30% of the patients, but this percentage is increasing gradually with newer, narrower, instruments and staff training in diagnostic and operative hysteroscopy [13,14]. Hysteroscopy can be performed on an outpatient basis or as a day case procedure with high acceptability and satisfaction from patients [15,16]. It also has the advantage of being able to treat endometrial pathology at the same time as diagnosing endometrial polyps or submucous fibroids, and endometrial ablation is an alternative to hysterectomy in many cases [17][18][19][20].…”
Section: Discussionmentioning
confidence: 91%
“…The objective of this study was to investigate, by hysteroscopy and endometrial biopsy, the causes of AUB in perimenopausal patients on sequential or continuous HRT regimens by comparing them with the causes of postmenopausal bleeding observed in another group of patients. In addition, this study emphasizes the increasing use of outpatient hysteroscopy as an effective and acceptable method for treating patients with bleeding problems [5].…”
Section: Introductionmentioning
confidence: 89%
“…It has improved our clinical management of postmenopausal bleeding, by providing information about endometrial thickness [2], evaluation of pelvic masses, by identifying their origin and nature [3,4], menstrual dysfunction, by identifying the presence, position and size of fibroids or intrauterine polyps [5], pelvic pain, by identifying the presence of ovarian pathology [6], and subfertility, by excluding hydrosalpinges and documenting polycystic ovaries [7]. These conditions are predominantly managed in general gynaecology clinics, although some of them have been managed in one-stop clinics [8,9]. These clinics allow a diagnosis to be made and a management plan to be formulated and discussed at a single visit.…”
Section: Introductionmentioning
confidence: 99%